Academic Service Learning for Sensitizing BEd Undergraduates on the Future Professional Role: A Design Based Research Initiative - Vithanapathirana, Manjula (My University, 2012)
Improving teacher quality is a recurring problem. Although a number of teacher development programs prevail in Sri Lanka, new initiatives are sought to improve the quality of teachers (World Bank, 2011). Academic service is a teaching method which promotes student learning through active participation in meaningful planned service to the community related to course content. It is founded on theories of experiential learning, transformation theory, critical reflection and education as preparation for civic responsibility (The Design-Based Research Collective, 2003). This study was an outcome of the exposure to service leaning in California State University (CSU), Chico, USA during the United States Institutes for Scholars program in 2011. The service learning program in CSU is not confined to teacher education but open to all undergraduates. Service learning is absent in teacher education programs in Sri Lanka. This study focuses on the exploratory design process of an intervention to be implemented in the BEd program conducted by the Faculty of Education, University of Colombo. Research questions are: 1. How does academic service learning in teacher education pose as an effective strategy for linking theory and practice? 2. What are the service learning interventions in teacher education reported in literature? 3. How could service learning interventions be introduced in the BEd program?